Homosexual University Students’ Perceptions of the Marriage Equality Referendum in Taiwan - Lin, Yii-nii; Chen, Wei-Chi; Liu, Hsin-Yu (Journal of Gender and Power, 2024)
This study examined the perceptions of 12 homosexual university students regarding Taiwan’s marriage equality referendum (MER) held in November, 2018. Semi-structured interviews were conducted to collect data, and the phenomenological approach was employed for data analysis. Four themes emerged from the data: reactions to the outcomes of the MER, emotional responses before and after the MER, perspectives on the MER, and self-reflection following the MER. The present findings have implications for counseling and education professionals as well as undergraduates in terms of homosexual students’ perceptions regarding the MER and how they coped with stress following the MER. These findings also serve to reminder policy-makers of the importance of protecting and advancing human rights and gender equality.